Forest road network in the Republic of Croatia – Status and perspectives - Tibor Pentek; Hrvoje Nevečerel; Dragutin Pičman; Tomislav Poršinsky (Croatian Journal of Forest Engineering, 2007)
Forest traffic infrastructure is one of the basic preconditions for good quality forest ecosystem management. Since 1991, when the Republic of Croatia gained independence and the company Hrvatske šume d.o.o. Zagreb (then Public Enterprise Hrvatske Šume Zagreb) was founded, a large amount of financial resources has been invested in the construction of new and the maintenance and repair of the existing forest roads. Despite considerable past investments in this forestry segment, many more kilometres of forest roads will have to be built until optimal forest openness is achieved. This article analyzes the situation with regard to forest roads in Croatia and focuses on the current state of openness, planned openness, annual construction plans, average construction costs, design costs and others. Problems occurring in the procedure of opening up forests (planning, design, construction with supervision and maintenance) are defined and some basic guidelines for their solution proposed.